Current therapy for bronchiolitis. Issue 9 (25th June 2012) - Nagakumar, Prasad; Doull, Iolo
Abstract : Bronchiolitis is a common, self-limiting, seasonal viral respiratory tract infection in infancy accounting for the majority of hospital admissions in this age group. Supportive care is the mainstay of treatment, concentrating on fluid replacement, gentle suctioning of nasal secretions, prone position (if in hospital), oxygen therapy and respiratory support if necessary. There is a long history of pharmacological agents offering no benefit in acute bronchiolitis. More recently, nebulised epinephrine has been demonstrated to offer short term benefits, while two stratagems have shown promise in decreasing risk of hospitalisation and length of hospital stay. The combination of oral dexamethasone with nebulised epinephrine potentially decreases the need for hospitalisation, while nebulised 3% hypertonic saline mixed with a bronchodilator decreases the length of hospitalisation. Although both stratagems appear safe and well tolerated, their role in clinical practice remains unclear.